2012
DOI: 10.1194/jlr.m027102
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxysterols in control of endothelial stiffness

Abstract: Multiple studies have shown that oxidative modifi cations of LDL (oxLDL) are a major factor in the development of atherosclerosis ( 1-6 ). The level of oxLDL increases dramatically with hypercholesterolemia in animal models of atherosclerosis ( 7,8 ), and in humans ( 9, 10 ), it is found in atherosclerotic lesions ( 11 ). It is also well established that dyslipidemia-induced dysfunction of vascular endothelial cells is a critical step in the early stage of atherosclerosis (e.g., Refs. 12-14 ) and a strong pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 71 publications
7
49
2
1
Order By: Relevance
“…Our previous studies showed that endothelial cell stiffening induced by the incorporation of oxysterols could be reversed by loading the cells with cholesterol (14). Here, we showed that cholesterol loading had the same effect on oxPAPC-induced endothelial cell stiffening (Fig.…”
Section: Oxpc-induced Disruption Of Lipid Packing Is Accompanied By Esupporting
confidence: 65%
See 4 more Smart Citations
“…Our previous studies showed that endothelial cell stiffening induced by the incorporation of oxysterols could be reversed by loading the cells with cholesterol (14). Here, we showed that cholesterol loading had the same effect on oxPAPC-induced endothelial cell stiffening (Fig.…”
Section: Oxpc-induced Disruption Of Lipid Packing Is Accompanied By Esupporting
confidence: 65%
“…In contrast to the previous belief, exposing endothelial cells to oxLDL does not result in cholesterol loading of endothelial cells but, instead, results in a decrease in lipid order of the cell membrane (11). A similar effect is observed in cells exposed to specific oxysterols (14). Thus, consistent with our findings on the effects of cholesterol depletion, exposure to oxLDL results in fluidization of the endothelial membrane accompanied by an increase in endothelial cell stiffness.…”
Section: Introductioncontrasting
confidence: 45%
See 3 more Smart Citations